2008
DOI: 10.1103/physreve.77.011923
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic range of hypercubic stochastic excitable media

Abstract: We study the response properties of d-dimensional hypercubic excitable networks to a stochastic stimulus. Each site, modeled either by a three-state stochastic susceptible-infected-recovered-susceptible system or by the probabilistic Greenberg-Hastings cellular automaton, is continuously and independently stimulated by an external Poisson rate h. The response function (mean density of active sites rho versus h) is obtained via simulations (for d=1,2,3,4) and mean-field approximations at the single-site and pai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…This signal compression property, or enhancement of dynamic range, is a general property of excitable media and has proven very robust against variations in the topology of the medium and the level of modeling, from cellular automata to compartmental conductance-based models [21][22][23][24][25][26][27][28][29][30][31][32][33]. Furthermore, the idea that dynamic range can be enhanced in neuronal excitable media has received support from experiments in very different setups [34,35], which again suggests that the phenomenon is robust.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This signal compression property, or enhancement of dynamic range, is a general property of excitable media and has proven very robust against variations in the topology of the medium and the level of modeling, from cellular automata to compartmental conductance-based models [21][22][23][24][25][26][27][28][29][30][31][32][33]. Furthermore, the idea that dynamic range can be enhanced in neuronal excitable media has received support from experiments in very different setups [34,35], which again suggests that the phenomenon is robust.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic range is one of the features of the response function which has received attention in the literature in recent years [21][22][23][24][25][26][27][28][29][30][31][32][33]35]. Here it serves the purpose of summarizing the quality of the EW mean-field approximation in comparison with model simulations.…”
Section: Excitable-wave Mean-field Approximationmentioning
confidence: 99%
“…4). For the multi-dimensional case, mean-field approximations also exist to determine the maximum dynamic range a system can attain [38]. Our results demonstrate that the dynamic range of young neurons decreases as more dendritic compartments are removed.…”
Section: Discussionmentioning
confidence: 91%
“…They also tell us that these results are robust for larger values of M and qualitatively similar for ρ < 1. This edge of chaos is particularly interesting, since it has been shown that this kind of transition can be optimal for certain magnitudes such as computational capacity [11] and dynamic range of sensitivity to stimuli [12]. To illustrate how this is also the case here, we store a set of M patterns and then show the system a randomly chosen one every certain number of time steps.…”
Section: Model and Resultsmentioning
confidence: 99%